Pembelajaran Relief Plastisin Kelompok B di TK Negeri Pembina Singaraja - ., Dedy Nur Saputra; ., Dra. Luh Suartini; ., Drs. Gede Eka Harsana Koriawan, M.Erg (Universitas Pendidikan Ganesha, 2017)
Penelitian ini bertujuan untuk, (1) Mengetahui alat dan bahan yang dipergunakan dalam pembelajaran relief plastisin di TK Negeri Pembina Singaraja (2) Mengetahui proses pelaksanaan pembelajaran relief plastisin di TK Negeri Pembina Singaraja, dan (3) Mengetahui hasil karya pembelajaran relief plastisin anak–anak di TK Negeri Pembina Singaraja. Penelitian ini merupakan penelelitian survei dengan pendekatan deskriptif kualitatif, penelitian dilakukan melalui wawancara dan penyebaran angket, dilanjutkan dengan observasi dan dokumentasi. Hasil Penelitian yang diperoleh, (1) Alat dan bahan yang digunakan dalam pembelajaran relief plastisin di TK Negeri Pembina Singaraja antara lain alat (gergaji, kater, ember, penggaris, pensil), bahan (plastisin, triplek). (2) Proses pembelajaran relief plastisin dilakukan dengan metode demonstrasi. Guru menyiapkan media dan perlengkapan pembelajaran, kemudian mendemonstrasikan cara penggunaan media, serta membimbing siswa dalam pembelajaran relief plastisin, selesai pembelajaran, guru melakukan evaluasi terhadap karya anak-anak. (3) Hasil karya relief plastisin anak-anak kelompok B4 TK Negeri Pembina Singaraja beranekaragam. Sesuai dengan kurikulum di sekolah (rumah, pemandangan alam laut, kebudayaan, tumbuhan, hewan) kemudian dianalisis menurut teori perkembangan kesenirupaan anak Victor Lowenfield dan diperoleh hasil sebagian besar karya anak-anak TK Negeri Pembina Singaraja sudah sangat baik dengan penguasaan garis, warna, ruang/bidang serta tema yang diajarkan di sekolah. Kata Kunci : Pembelajaran, relief, plastisin. This study aimed to investigate certain objectives of study, namely: (1) to know tools and materials used in the learning of plasticine relief at TK Negeri Pembina Singaraja; (2) to know a process of implementation of learning plasticine relief at TK Negeri Pembina Singaraja; (3) to know students’ results of performances in learning plasticine relief at TK Negeri Pembina Singaraja. This study used a survey research using a qualitative research approach to conduct the study. In addition, this study was executed by applying interviews, questionnaires, observations, and documentations. The study shows certain results of investigation, namely: (1) in learning plasticine relief, saw, knife, bucket, ruler, and pencil belonged to tools of learning; whilst, plasticine and plywood belonged to materials of learning. (2) Process of learning plasticine relief was conducted in demonstration method. In relation to this point, a teacher prepared learning media and others learning equipment; demonstrated ways of using leaning media; and, guided students in learning plasticine relief. At the end of the class, the teacher conducted an evaluation toward students’ results of performances. (3) Results of students’ performances were diverse related to certain themes used, such as: houses, ocean sceneries, cultures, trees, and animals. Furthermore, results of students’ performances were analyzed based on theory of development of childhood art stated by Victor Lowenfield. Moreover, results of data analysis shows that most results of students’ performances are very good in related to certain applications of elements, like lines, colors, spaces/fields, and themes. keyword : learning, relief, plasticine